1 - Zahwa, Giska Khaylila; Sari, Syavira Ruwina; Lathifah, Syifa Aufa; Karimah Baihaqie, Natasya Fidyah; Padmasari, Indira (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Ethical finansial management is one of the important factors for the sustainability of micro, small, and medium enterprises (MSMEs). Business ethics in finansial management can be seen through honesty in recording transactions, the use of finansial data in business decision-making, and regular finansial evaluation. This study aims to examine the implementation of business ethics in MSME finansial management and to compare its application between star-up MSMEs and branch-based MSMEs. This research uses a quantitative descriptive method, with data collected through] questionnaires distributed to 32 MSME owners. The collected data were analyzed to identify differences in the application of business ethics between thye two types of MSMEs. The results show that branch-based MSMEs tend to have more organized and ehical finansial management compared to strt-up MSMEs, especially in terms of finansial record-keeping and the use of finansial data as a basis for business decisions. This indicates that business experience and more structured management systems influence the application of business ethicts in MSME finansial management.